Insights into cognitive and behavioral comorbidities of SLC6A1-related epilepsy: five new cases and literature review - Trivisano, Marina; Butera, Ambra; Quintavalle, Chiara; De Dominicis, Angela; Calabrese, Costanza; Cappelletti, Simona; Vigevano, Federico; Novelli, Antonio; Specchio, Nicola (Frontiers in Neuroscience, 2023)
Introduction SLC6A1 pathogenic variants have been associated with epilepsy and neurodevelopmental disorders. The clinical phenotype includes different seizure types, intellectual disability, and psychiatric symptoms affecting mood and behavior. Few data regarding neuropsychological features have been described, and details on cognitive profiles are often missing due to the lack of standardized tests. Methods We retrospectively reviewed the neuropsychological assessments of five subjects carrying heterozygous missense genetic variants in SLC6A1. We also collected data on epileptic features, EEGs, and brain MRIs. Additionally, we reviewed neuropsychological data from 204 previously reported patients with SLC6A1 pathogenic variants. Results In our series, at the last evaluation (median 12.6 years), three patients had borderline intellectual functioning, one patient had mild cognitive impairment, and one patient presented with a moderate cognitive disability. Three out of five patients underwent at least two neuropsychological evaluations, which revealed a worsening of cognitive functions over time. We detected attention deficits in all patients. In addition, we observed anxiety, disruptive behavior disorder, emotional instability, and hetero aggressiveness. We also performed a literature review that highlighted that most of the patients with SLC6A1 pathogenic variants have mild-to-moderate intellectual disability and that one-third of cases have autistic traits. Discussion Based on the literature review and the detailed description of our cases, we conclude that patients with SLC6A1-related epilepsy mostly present with mild-to-moderate intellectual disability, often associated with attention disorders. Such symptoms may worsen over time. Periodic standardized neuropsychological tests may be useful tools to follow development over time, and patient-specific rehabilitation programs could be tailored consistently.